Impact of War on the Natural Preserve Fund: Challenges for the Development of Ecological Tourism and Environmental Protection - KUCHER, Anatolii; HONCHAROVA, Anna; KUCHER, Lesia; BIELOBORODOVA, Mariia; BONDARENKO, Liudmyla (Journal of Environmental Management and Tourism, 2023)
The global deterioration of the quality of the natural environment causes an increase in the importance of ecological tourism, primarily at the sites of the nature reserve fund. This paper is one of the first attempts to fill the existing gaps in the question of the impact of war on protected natural areas. The article determines the development trends, current state, and problems of the objects of the nature reserve fund in Ukraine in the conditions of unjustified full-scale russian military aggression and makes an approximate calculation of the damages caused as a result of hostilities. It was established that during 2012–2020, the number of objects of the nature reserve fund in Ukraine increased by 605 units or by 7.5 %; the area of these objects increased by 562,460.6 hectares or by 14.3 %. Due to russian military aggression, danger threatens 900   protected areas, which is 1.2 million hectares or about 30 % of the area of all protected areas of Ukraine. The damage calculation was carried out on the example of the Feldman EcoPark regional landscape park in the Dergachy district of the Kharkiv region. It was established that the approximate estimate of damages from the loss of ecosystem services of this landscape park as of 20.05.2022 was 16,979.5 thousand USD, including in terms of ecosystem services: (i) recreation and ecotourism – 13,846.2 thousand USD; (ii) air purification from solid fine particles and harmful gases – 272.1 thousand USD; (iii) biodiversity habitat – 2,861.3 thousand USD. In addition, the amount of damage caused to the regional landscape park due to the loss of animals, calculated based on special fees for calculating the amount of damage to the nature reserve fund, amounts to 63,350 USD. The determined damage estimates are preliminary and need to be clarified after the end of the war.